2015
DOI: 10.1155/2015/210784
|View full text |Cite
|
Sign up to set email alerts
|

Improved Enzyme Catalytic Characteristics upon Glutaraldehyde Cross-Linking of Alginate Entrapped Xylanase Isolated fromAspergillus flavusMTCC 9390

Abstract: Purified fungal xylanase was entrapped in alginate beads. Its further cross-linking using glutaraldehyde resulted in large enzyme aggregates which may function as both a catalyst and a support material for numerous substrate molecules. Enzyme cross-linking presented a negative impact on enzyme leaching during repeated washings and recovery of enzyme activity was substantial after twelve cycles of usage. The entrapment followed by cross-linking doubled the total bound activity and also greatly improved the enzy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 36 publications
5
34
0
1
Order By: Relevance
“…They indicated that the H + in the fermentation broth diffused freely to the inside of the immobilized cell particles through the large pores of the calcium alginate matrix and caused a change in charge quantities of the plasma membrane, which led to a change in the permeability of the plasma membrane to nutrients and inorganic salt ions, affecting the fermentation efficiency. Another research showed that extreme acidic pH caused changes in intracellular ionic environment and damages to protein structure, which was detrimental to cell growth and metabolism, leading to a decrease in product yield and productivity (Bhushan et al 2015). It has also been reported that the inhibitory effect of LA with the undissociated form on LA production is more significant than that of the dissociated lactate form if the pH is closer to the pKa of LA (about 3.9) (Pal et al 2009).…”
Section: Effect Of Parameters On Immobilized L Pentosus Atcc 8041 Cementioning
confidence: 99%
“…They indicated that the H + in the fermentation broth diffused freely to the inside of the immobilized cell particles through the large pores of the calcium alginate matrix and caused a change in charge quantities of the plasma membrane, which led to a change in the permeability of the plasma membrane to nutrients and inorganic salt ions, affecting the fermentation efficiency. Another research showed that extreme acidic pH caused changes in intracellular ionic environment and damages to protein structure, which was detrimental to cell growth and metabolism, leading to a decrease in product yield and productivity (Bhushan et al 2015). It has also been reported that the inhibitory effect of LA with the undissociated form on LA production is more significant than that of the dissociated lactate form if the pH is closer to the pKa of LA (about 3.9) (Pal et al 2009).…”
Section: Effect Of Parameters On Immobilized L Pentosus Atcc 8041 Cementioning
confidence: 99%
“…In this study, 3% of sodium alginate concentration was suitable for enzyme immobilization ( Table 2). This may be due to the formation of strong cross linked gel and entrapment of enzyme [30,31]. Studies of different concentration (0.05-0.5 M) of CaCl 2 showed that 0.2 M retained maximum immobilization yield ( Table 2).…”
Section: Effect Of Sodium Alginate and Cacl2 Concentration On Xylanasmentioning
confidence: 99%
“…Moreover, hyaluronic acid was chemically cross‐linked with glutaraldehyde to form insoluble films (Tomihata and Ikada ). Enzyme can also be cross‐linked with alginate beads using glutaraldehyde (Bhushan and others ). The mechanical properties of 2 cross‐linked molecular weight pullulan films with or without glycerol as a plasticizer at various concentrations of glutaraldehyde are summarized in Table .…”
Section: Resultsmentioning
confidence: 99%